Development of SKI Phase D Learning Media Gamification-based - Bagas Nirwana Selian; Zulfatmi, Zulfatmi; Hayati, Hayati; Nurbayani, Nurbayani (Department of Islamic Education, Postgraduate Program Univercity for Islamic Studies Palu, 2025)
This article aims to develop gamification-based learning media in learning Islamic Cultural History (SKI) in phase D (equivalent to classes VII and IX MTs) using the Research and Development (R&D) method with the ADDIE model. The focus of the discussion is on analyzing development needs which include identifying media needs in learning, student characteristics, and the nature of SKI material through observation, interview and document review techniques. The results revealed that SKI learning is considered boring due to monotonous conventional methods, while students are more interested in visual and narrative material such as the historical story of the Prophet Muhammad, despite having difficulty with complex material such as the development of Islam in the archipelago; both teachers and students appreciate the potential of gamification media with elements of levels, challenges, rewards, and leaderboards to increase motivation and learning engagement. The research conclusion shows that gamification-based media can be an innovative solution to create more interesting, interactive, and meaningful SKI learning while integrating Islamic values and 21st century skills, so further development is recommended to ensure its effectiveness and sustainability in various learning contexts.